Tindak Pidana Hate Speech Ditinjau dari Hukum Pidana dan Konstitusi - Hartarto Pakpahan (Jurnal Cakrawala Hukum, 2018)
The development of information technology has changed the lifestyle (life style) for the people of Indonesia, including in expressing their opinions through various kinds of social networking sites such as face book, instagram, twiter, whatsapp and various other types of social media. Opinion through social media often often intentionally or unintentionally contains content of hate speeches which then also lead to punishment. Even though from the point of view of criminal law, it has regulated and also threatens a criminal sentence that is quite severe for people who conduct hate speeches. From the point of view of Constitutional Law the act of expressing an opinion / thought is not a crime or a crime because such action is an act protected by the laws and parts of human rights as stipulated in 28E and 28F of the 1945 Constitution. That is what makes expressions of expression a despicable or evil act and also contrary to the constitution because of the impact of hatred on certain people or groups, hate speech has the potential to cause hate crimes.How to cite item: Pakpahan, H. (2018). Tindak Pidana Hate Speech Ditinjau dari Hukum Pidana dan Konstitusi. Jurnal Cakrawala Hukum, 9(2), 168-176. doi:https://doi.org/10.26905/idjch.v9i2.2771